Light source selection for a solar simulator for thermal applications: A review - Tawfik, Mohamed M.; Tonnellier, Xavier; Sansom, Christopher L. (Elsevier, 2018)
Solar simulators are used to test components and systems under controlled and repeatable conditions, often in locations with unsuitable insolation for outdoor testing. The growth in renewable energy generation has led to an increased need to develop, manufacture and test components and subsystems for solar thermal, photovoltaic (PV), and concentrating optics for both thermal and electrical solar applications. At the heart of any solar simulator is the light source itself. This paper reviews the light sources available for both low and high-flux solar simulators used for thermal applications. Criteria considered include a comparison of the lamp wavelength spectrum with the solar spectrum, lamp intensity, cost, stability, durability, and any hazards associated with use. Four main lamp types are discussed in detail, namely argon arc, the metal halide, tungsten halogen lamp, and xenon arc lamps. In addition to describing the characteristics of each lamp type, the popularity of usage of each type over time is also indicated. This is followed by guidelines for selecting a suitable lamp, depending on the requirements of the user and the criteria applied for selection. The appropriate international standards are also addressed and discussed. The review shows that metal halide and xenon arc lamps predominate, since both provide a good spectral match to the solar output. The xenon lamp provides a more intense and stable output, but has the disadvantages of being a high-pressure component, requiring infrared filtering, and the need of a more complex and expensive power supply. As a result, many new solar simulators prefer metal halide lamps.
Keywords: Tungsten lamp; CSP; Solar simulator; Metal halide; Sunlight; Solar spectrum